The 3D leader : take your leadership to the next dimension - Mauri, Terence (Pearson, 2020)
"Reading this new book will help you do the following: Use a powerful and proven 3D Leader System to launch bold, scale brave and go beyond by a factor of 10. Unlock a new leadership mindset for learning, growth and change Build a challenge culture where it's safe to speak up and bring your best and boldest self to work Adapt to the speed and complexity of change Own the future rather than be disrupted by it"--